Impact of COVID-19 on glaucoma management: A review - Yadav, Manoj; Tanwar, Mukesh (Frontiers in Ophthalmology, 2022)
Glaucoma is the leading cause of irreversible vision loss and the second leading cause of blindness worldwide. The rapid transmission of SARS-CoV-2virus compelled governments to concentrate their efforts on emergency units to treat the large number of cases that arose due to the Covid-19 outbreak. As a result, many chronically ill patients were left without access to medical care. The progression of glaucoma in previously diagnosed cases has been accelerated; due to this, some have lost their vision. Evaluation of Covid-19's effect on glaucoma treatment was one goal of this study. We used search phrases like "COVID-19," "telemedicine," and "glaucoma" to find published papers on COVID-19 and glaucoma. Artificial Intelligence (AI) may be the answer to the unanswered questions that arose due to this pandemic crisis. The benefits and drawbacks of AI in the context of teliglaucoma have been thoroughly examined. These AI-related ideas have been floating around for some time. We hope that Covid-19's enormous revisions will provide them with the motivation to move forward and significantly improve services. Despite the devastation the pandemic has caused, we are hopeful that eye care services will be better prepared and better equipped to avoid the loss of sight due to glaucoma in future.